Isolation of vaccinia JX594 from pustules following therapy for hepatocellular carcinoma. Issue 1 (December 2015) - Kung, Che-Hsuan; Kuo, Shu-Chen; Chen, Te-Li; Weng, Wen-Sung
Abstract Background JX594 is an oncolytic poxvirus derived from Wyeth strain vaccinia virus. We reported the presentation of cutaneous and mucosal pustules containing laboratory-confirmed JX594 in a patient following injection of JX594. Case presentation A 36-year-old man was diagnosed hepatitis B virus-associated hepatocellular carcinoma on September 19, 2011. Despite treatment with entecavir, radiofrequency ablation and transarterial chemoembolization for recurrent local tumors, the tumors recurred in both lobes and lung metastases were detected by computed tomography on September 12, 2012. The patient was treated with JX594 (Pexa-vec®) via intravenous injection on December 19, 2012. No apparent adverse effects were observed following intravenous injection other than a single fever episode. However, pustular lesions were detected on both sides of the tongue dorsum and on the proximal interphalangeal joint of the right middle finger on December 25, 1012. Biopsy samples analyzed by PCR identified the presence of the JX-594-specific hGM-CSF transgene and the disrupted viral thymidine kinase gene. Following aspiration of the lesion a scab formed that resolved within 14 days without necessitating additional treatment. Conclusion Our case completely recovered and did not develop systemic or recurrent disease, the presentation of a few pustules may not necessarily require that treatment with JX594 be interrupted for patients with advanced hepatocellular carcinoma.